Concepto y Régimen Jurídico del Servicio Público en el Ordenamiento Público Peruano - Huapaya Tapia, Ramón (2015)
The author proposes a review of the different experiences relating to public services of economic content, both nationally and internationally, and then he analyze its concept and legal framework in national law. to this end, he reviews therecent literature on the subject, the constitutional basis and the relevant case law in order to offer his concept of Guarantor state , linked to the role and concept of public service in the peruvian legal system.